2013
DOI: 10.1186/1471-230x-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Laxative effects of Salecan on normal and two models of experimental constipated mice

Abstract: BackgroundConstipation is one of the most common gastrointestinal complaints with a highly prevalent and often chronic functional gastrointestinal disorder affecting health-related quality of life. The aim of the present study was to evaluate the effects of Salecan on fecal output and small intestinal transit in normal and two models of drug-induced constipation mice.MethodsICR mice were administrated intragastrically (i.g.) by gavage with 100, 200 and 300 mg/kg body weight (BW) of Salecan while the control mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…These properties suggested that Salecan could be utilized in the food industry as a new source of thickening agent and medical industry for preventing and treating constipation. [29][30][31][32][33][34] In addition, Salecan affords a high density of hydroxyl groups, which can be modied to provide greater exibility in the preparation of hydrogels. Recently, Salecan-based hydrogels were successfully fabricated in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…These properties suggested that Salecan could be utilized in the food industry as a new source of thickening agent and medical industry for preventing and treating constipation. [29][30][31][32][33][34] In addition, Salecan affords a high density of hydroxyl groups, which can be modied to provide greater exibility in the preparation of hydrogels. Recently, Salecan-based hydrogels were successfully fabricated in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of salecan is a linear (1→3)-␤-d-glucan consisted of ␤-1-3-linked glucopyranosyls with a small quantity of ␣-1-3-linked [33]. As a novel polysaccharide, salecan has been utilized in the fields of both food and medical in our laboratory [34][35][36][37][38]. With a high density of hydroxyl groups, the large molecular weighted (2 × 10 6 Da) salecan could be further modified for multifarious applications.…”
Section: Introductionmentioning
confidence: 99%
“…The method to evaluate the prokinetic and laxative effects on small intestinal transit and fecal output character in normal and two models of experimental constipated mice were based on previous reports (Xu et al, 2012, Zhou et al, 2013, Shan et al, 2010. Briefly, fifty animals were randomly divided into five groups (5 male and 5 female each group): normal group, Neosigmine Methylsuifate group (NM), and three doses of EXQ groups (2.92, 4.38 and 6.75 g/kg).…”
Section: Small Intestinal Transit Rates In Normal Micementioning
confidence: 99%
“…Constipation, defined as infrequent or difficult defecation, is one of the most common dysfunctional gastrointestinal symptoms in both developed and developing countries (Zhou et al, 2013). Constipation occurs in up to 27% of the general population and affects all age groups (Longstreth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%